ENVIRONMENTAL PROTECTION AS A FACTOR OF AGRICULTURAL DEVELOPMENT IN THE REPUBLIC OF SERBIA - Vladimir Šebek (Ekonomika Poljoprivrede (1979), 2020)
Public concern about the environmental impact of economic activities has significantly increased around the globe in recent years. Within the scope of unlawful acts, environmental delicts are among the most serious ones in terms of environmental impact, the consequences of which directly affect the quality and development of agriculture as the main branch of economic activity.